Growth Mechanism and Carbon Sequestration of Gracilaria verrucosa - Wahdaningsih, Sri Muliani; Mulyani, Sri; Salam, Suryawati (Universitas Diponegoro, 2025)
Gracilaria verrucosa, a commercially valuable red macroalga, plays a pivotal role in coastal aquaculture and carbon sequestration. This study investigates the effects of varying initial seedling weights (50 gram, 75 gram, 100 gram, and 125 gram/tie) on biomass yield, specific growth rate (SGR), and carbon sequestration over a 49-day cultivation period. Conducted in a floating raft system under controlled coastal conditions in South Sulawesi, Indonesia, the experiment followed a completely randomized design (CRD) with three replications per treatment. Biomass was harvested at seven-day intervals and assessed for dry weight, growth rate, and carbon composition using standardized methods and elemental analysis protocols. The results indicate that the 125 grams/tie treatment yielded the highest biomass, suggesting that larger initial weights enhance growth through enhanced nutrient uptake. However, the highest SGR and carbon sequestration were recorded in the 50 grams/tie treatment, highlighting the impact of planting density on physiological performance and carbon sequestration. The 100 grams/tie treatment presented the most balanced profile, maintaining high biomass while avoiding significant declines in SGR or carbon sequestration. These findings reveal a critical trade-off between economic and ecological outcomes, with implications for seaweed-based climate mitigation strategies and sustainable aquaculture design. Optimizing planting density can improve both yield and ecosystem services, aligning cultivation strategies with environmental sustainability objectives.